Representations of immigration and the border fence: an evaluation of media frames in two U.S. newspapers - Rodríguez-Escobar, Manuel A., author; Dickinson, Greg, advisor; Sagás, Ernesto, committee member; Aoki, Eric, committee member (Colorado State University. Libraries, 2010)
On October 26, 2006, President George W. Bush enacted the Secure Fence Act in response to what many congressional members and U.S. citizens deemed a growing immigration problem. In the months immediately preceding and following the authorization of the bill, various discourses arose across the nation to engage in a growing debate on ways to solve the perceived dilemmas caused by immigration. This study evaluated and compared the dialogues engaged within two U.S. newspapers to determine how the news outlets described and discussed immigration. More specifically, this study first explored news reports found in the Washington Post, since this newspaper serves as the leading periodical in the Washington D.C. area, where the Secure Fence Act was debated amongst journalists, politicians, and lobbyists. Next, this project investigated newspaper articles found in the Brownsville Herald, which serves a targeted audience living along the U.S.-Mexico border. The goal of this investigation was to compare the two divergent discourses in order to identify the common themes and frames employed by media outlets to describe immigrants and immigration. This study incorporated theories of frame and metaphorical analysis to determine the common themes utilized by journalists, politicians, and lobbyists in their descriptions of immigrants and immigration. Additionally, this project surveyed articles that included the key terms "immigration" and "border fence" in order to narrow the sample on dialogues centered around the passage of the Secure Fence Act. Lastly, this examination explored articles published in the three months prior to and three months following the enactment of the Secure Fence Act to best gauge suggestions, responses, and reactions to the U.S. governments' response to the perceived immigration problem. The findings indicated that the two periodicals discussed immigration and offered representations of immigrants utilizing very different themes and metaphors, which raised concerns about whether the 109th Congress appropriately and effectively responded to the perceived immigration problem. The author suggests that frame and metaphorical analysis can be incorporated into future studies focused on understanding how a particular issue is represented within a variety of media outlets. The author's hope is that understanding the various sides and concerns of any particular issue can lead to a more productive dialogue on how to most effectively resolve the problems identified by various communities.
Department Head: Sue Pendell.